THE USE OF HERBAL MOUTHWASH THERAPY IN ORAL LICHEN PLANUS: A SYSTEMATIC REVIEW - SANTO, AGUSTIN NININTOWE T.; DEWI, TENNY SETIANI; HIDAYAT, WAHYU (International Journal of Applied Pharmaceutics, 2022)
This study aid to describe the advantages of herbal mouthwash therapy in Oral Lichen Planus (OLP). This systematic review was carried out using PRISMA methods. The selected articles were published in the last five years from PubMed and Google Scholar with the keywords mouthwash, mouth rinse, and Oral Lichen Planus was conducted in June 2022. The assessment of the risk of bias uses the Oxford Scoring System. A total of 2225 journals were found, and seven articles were obtained through screening. After the risk of bias assessment, six articles of high-range quality and one article of low-range quality were obtained. The six journals are randomized clinical trials of herbal mouthwashes and synthetic mouthwashes. Three articles on herbal mouthwash, two articles on synthetic mouthwash, and one article comparing herbal and synthetic mouthwashes. These articles show differences in the time, size, and pain of using herbal and synthetic mouthwashes; they also found side effects when using synthetic mouthwashes compared to herbal mouthwashes. Herbal mouthwash has fewer side effects than synthetic mouthwash, although clinically, synthetic mouthwash is more effective than herbal mouthwash.